Trillion Game. Volume 10 - Inagaki, Riichiro (VIZ Media, LLC, 2026)
"Self-proclaimed "world's greediest man" Haru and timid computer whiz Gaku set out to make a trillion dollars. They start the company Trillion Game to accomplish this task and hope to iron out the details as they go. With charm, technical skills, and no business plan, can these unlikely friends reach their lofty goal? Haru and Gaku have successfully pulled off a partnership with a major cellular provider. Now their enemy is Gokitsugu, emperor of the telecommunications world. With a trillion yen on the line, Trillion Game strikes back!" --